Flower palate structure of the aquatic bladderworts Utricularia bremii Heer and U. minor L. from section Utricularia (Lentibulariaceae) - Płachno, Bartosz J.; Stpiczyńska, Małgorzata; Krajewski, Łukasz; Świątek, Piotr; Adamec, Lubomír; Miranda, Vitor Fernandes Oliveira [UNESP] (Springer Nature, 2017)
There is an enormous diversity in the structure of the flower palate of the carnivorous rootless genus Utricularia. This study aims to examine the structure of the palates in Utricularia bremii Heer and U. minor L of the Utricularia sect. Utricularia, which have a glandular palate type. In both species, the palate has only one type of glandular trichomes. Because of the occurrence of cell wall ingrowths in its glandular cells, any exudation may be transported via eccrinous secretion. It was proposed that the palate trichomes of the examined species act as scent glands and that the palate may play a role as an unguentarium. Both U. bremii and U. minor are of an open flower type. Thus, U. bremii and U. minor flowers can be penetrated by small, weak insects, which then easily have access to their generative structure. Small Hymenoptera (member of families Mymaridae and Braconidae) were observed as flower visitors of the male-sterile species Utricularia bremii.
Keywords: Bladderwort; Carnivorous plant; Floral micro-morphology; Lentibulariaceae; Osmophore; Pollination; Sect. Utricularia; Ultrastructure